1997
DOI: 10.1063/1.365878
|View full text |Cite
|
Sign up to set email alerts
|

Shock-induced chemical reactions in titanium–silicon powder mixtures of different morphologies: Time-resolved pressure measurements and materials analysis

Abstract: The response of porous titanium (Ti) and silicon (Si) powder mixtures with small, medium, and coarse particle morphologies is studied under high-pressure shock loading, employing postshock materials analysis as well as nanosecond, time-resolved pressure measurements. The objective of the work was to provide an experimental basis for development of models describing shock-induced solid-state chemistry. The time-resolved measurements of stress pulses obtained with piezoelectric polymer (poly-vinyl-di-flouride) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…Prior work on the Ti+Si system has revealed evidence of particlesize-dependent dynamic material response [5]. Recovery experiments performed on mixtures of Ti and Si (5:3 molar ratio) of varying particle sizes revealed distinct differences in the particle-level mechanical behavior of the components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior work on the Ti+Si system has revealed evidence of particlesize-dependent dynamic material response [5]. Recovery experiments performed on mixtures of Ti and Si (5:3 molar ratio) of varying particle sizes revealed distinct differences in the particle-level mechanical behavior of the components.…”
Section: Introductionmentioning
confidence: 99%
“…Intermediate particle sizes (< 45µm) exhibited simultaneous deformation and mixing. These disparate micromechanical behaviors exact direct influence over the propensity for initiating ultra-fast shock-induced chemical reactions, with only the intermediate particle sizes displaying signatures of reaction, evidenced by increases in shock velocity above a threshold stress of 1.5 GPa [5].…”
Section: Introductionmentioning
confidence: 99%
“…According to Thadhani et al [6], Ti-Si could be reaction at the flyer velocity of <1.0km/s after enough ballmilling treatment for pre-activated powder mixture. However, to avoid pollution from impurity during the ball milling process, the mixtures of Ti and Si were directly shocked after pressing into the container.…”
Section: Resultsmentioning
confidence: 99%
“…8 While processes of thermal ignition in such reactive materials are well understood, 9 the mechanisms of impact-initiated reactions and their kinetics remain to be established. Our prior work 10,11,12 showed that shockinitiation of chemical reactions is influenced by differences in the elastic/plastic properties of reactant materials and their morphological characteristics. Under uniaxial-strain loading, micro-size spherical Ni+Al powder mixtures showed crush-up to full density at ~0.5 GPa, while the crush-up stress for flake-Ni+Al mixtures of similar size is ~2 GPa, and that of nano-sized Ni+Al was ~6 GPa.…”
Section: Configurational Effects On Anaerobic Chemical Reactionsmentioning
confidence: 99%